DISCRIMINATION METHOD FOR GAMMA RAY DOSES IN NEUTRON FIELDS USING AN IONIZATION CHAMBER WITH ATTENUATION FILTERS. Issue 1 (6th February 2019) - Ogawara, R; Suda, M; Hagihara, T; Kodaira, S; Hamano, T
Abstract: Neutron fields produced by an accelerator-driven neutron source are generally mixed radiation fields that consist of fast neutrons and gamma rays. To estimate the biological effects of fast neutrons precisely, the gamma ray dose contamination must be evaluated in neutron fields. In this work, we developed a discrimination technique for absorbed doses ( 60 Co gamma-ray equivalent) of fast neutrons and gamma rays using an ionization chamber. The filter thickness dependences of the absorbed doses of fast neutrons and gamma rays are different for a given filter material. Thus, the absorbed doses of each type of radiation were distinguished by fitting the dose attenuation curve, which was measured with an ionization chamber and attenuation filters, with a two-component exponential function. The absorbed dose of fast neutrons and gamma rays with no attenuation filter was evaluated from the y -intercept of the fitting function. This technique was demonstrated in two neutron fields produced by 4 MeV proton and deuteron bombardment of a 9 Be target. The thicknesses of the polyethylene attenuation filters were 0–350 mm. The dose attenuation coefficients of fast neutrons obtained by the two-component exponential fitting function for the 9 Be(p, n) 9 and 9 Be(d, n) reactions showed differences of 1.5 and 1.7%, respectively, from the reference measurements using a CR-39 plastic nuclear track detector. The absorbed dose contributions of gamma rays in neutrons fields of the 9 Be(p, n) 9 B and 9 Be(d, n) reactions were evaluated as 30.2 ± 3.24% and 20.4 ± 5.16%, respectively, without polyethylene filters.